Exploratory Psychometric Properties of the Farsi and English Versions of the Spiritual Needs Questionnaire (SpNQ) - Nejat, Nazi; Crowe, Marie; Whitehead, Lisa (2016)
The aim of this study was to translate and test the psychometric properties of a Farsi and an English version of the spiritual needs questionnaire (SpNQ) a measure originally developed in German. The World Health Organization guideline for translating and validating questionnaires was used. Participants were recruited from hospitals in Iran and New Zealand during an outpatient follow-up appointment after cancer treatment. People diagnosed with cancer in Iran (68) and New Zealand (54) completed and returned the SpNQ (at time 1) and within the two week time period (time 2). Cronbach's alpha ranged from 0.79 to 0.92, except for the existentialistic domain of the SpNQ (0.53-0.54). The coefficient of variation (CV) indicated minimal random variation between the assessments; the measures were generally stable, except for the item existentialistic. The translated versions of the SpNQ have the potential to support a comprehensive assessment of cancer patients' spiritual needs.
Keywords: Cancer; Needs; Spiritual Care